NOx related chemistry - Eldik, Rudi van; Olabe, Jose A. (Advances in inorganic chemistry, 2015)
NOx Related Chemistry is a volume of a series that presents timely and informative summaries of the current progress in a variety of subject areas within inorganic chemistry, ranging from bio-inorganic to solid state studies. This acclaimed serial features reviews written by experts in the field and serves as an indispensable reference to advanced researchers. Each volume contains an index, and each chapter is fully referenced.